2007
DOI: 10.1073/pnas.0700222104
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of hippocampal subfields to cortical up–down states

Abstract: The connectivity of the hippocampal trisynaptic circuit, formed by the dentate gyrus, the CA3 and the CA1 region, is well characterized anatomically and functionally in vitro. The functional connectivity of this circuit in vivo remains to be understood. Toward this goal, we investigated the influence of the spontaneous, synchronized oscillations in the neocortical local field potential, reflecting up-down states (UDS) of cortical neurons, on the hippocampus. We simultaneously measured the extracellular local f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 41 publications
13
95
3
Order By: Relevance
“…They reinforce novel views of slow waves as a global process spreading beyond the thalamocortical system in expanding loops (9,46,47). They also strengthen the view that the dynamics of depolarizing states in the striatum, which lacks an intrinsic excitatory driving force, depend highly on the dynamics of cortical networks (8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 66%
“…They reinforce novel views of slow waves as a global process spreading beyond the thalamocortical system in expanding loops (9,46,47). They also strengthen the view that the dynamics of depolarizing states in the striatum, which lacks an intrinsic excitatory driving force, depend highly on the dynamics of cortical networks (8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 66%
“…Our findings highlight the important role of slow hippocampal-cortical oscillatory activity in driving brain-wide rsfMRI connectivity and mediating sensory processing. studies also found similar slow oscillatory activities in the hippocampus (30,31). In particular, DG granule cells modulate hippocampal slow oscillations phase locked to neocortical slow oscillations with a short delay (31).…”
Section: Significancementioning
confidence: 61%
“…studies also found similar slow oscillatory activities in the hippocampus (30,31). In particular, DG granule cells modulate hippocampal slow oscillations phase locked to neocortical slow oscillations with a short delay (31). This dynamic property suggests that individual hippocampal neurons can form functional connections with other neurons to create synchronized networks, particularly in slow oscillation frequency ranges, to mediate complex cognitive functions.…”
Section: Significancementioning
confidence: 71%
“…Granule cells, the principal neurons of the DG, are excitatory cells with unique properties (Ylinen et al, 1995;Henze et al, 2002;Hahn et al, 2007;Leutgeb et al, 2007). Their highly specialized axonal output, the MFs (Frotscher et al, 2006;Rollenhagen et al, 2007), provide strong synaptic excitation to CA3 pyramidal cells, with the short-and long-term plasticity mechanisms involved in the MF-mediated excitation of target cells being distinct from the mechanisms involving inputs originating from other sources, including those from local pyramidal cells (Williams and Johnston, 1991;Jonas et al, 1993;Nicoll and Malenka, 1995;Salin et al, 1996;Maccaferri et al, 1998;Min et al, 1998;Nicoll and Schmitz, 2005;Pelkey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%